Integrating Qur'anic Narratives in English Language Teaching: Cultivating Moral Values Among Ninth-Grade Students - Nurhayati, Dwi Astuti Wahyu; Fibriani, Zeni Maulidiana (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
This study addresses the challenge of integrating moral education into English Language Teaching (ELT) in culturally diverse contexts. Using a mixed-methods approach, the research investigates the effectiveness of incorporating Qur'anic narratives into ELT to cultivate moral values among ninth-grade students at junior high school. The study involved 27 students and employed pre-test and post-test assessments, along with qualitative interviews. Findings reveal a significant improvement in students' moral reasoning and behavior, with post-test scores increasing from an average of 48.15 to 82.22. Thematic analysis identified key moral values internalized by students, including resilience, integrity, and faith. The research concludes that integrating culturally resonant narratives into ELT effectively fosters both linguistic and ethical development. These findings have important implications for curriculum development and teacher training, suggesting the need for a more holistic approach to language education that addresses both linguistic competencies and character development in culturally diverse educational settings. The study also highlights the potential of narrative pedagogy in creating meaningful learning experiences that resonate with students' cultural and religious backgrounds.